Appropriate criteria for a transition from conventional to sustainable warehousing - Vasileva, Anita (Logistics, supply chain, sustainability and global challenges, 2022)
This research paper conducts the process of selecting the criteria that are the most appropriate for a transition from conventional to sustainable warehousing. SWOT analysis is used to emphasise the weaknesses of conventional and the strengths of sustainable warehousing to select the most appropriate for the herein presented study. The results have been verified via a questionnaire filled out by professionals in economics, logistics and warehousing, and mechanical engineering. be added under the methodology section. The results gave the five most important criteria by transforming the conventional into sustainable warehousing. Finally, the paper concluded that renewable energy sources are the most important criteria for transforming by conventional to sustainable warehousing by environmental aspects, as well as the smart technology is above all other criteria by economic aspect. Moreover, providing personal protection equipment and servicing machinery and vehicle on regular basis are the two mainly criteria by social (safety) aspect.
Keywords: analiza SWOT; logistics; logistika; obnovljiva energija; renewable energy; sustainable warehousing; SWOT analysis; trajnostno skladiščenje